Biweekly CAPOX versus triweekly CAPOX in the adjuvant therapy of post-surgery CRC: A randomized controlled trial. - Hangyu Zhang; Danyang Wang; Zhou Tong; Tao Xiang; Xudong Zhu; Lulu Liu; Yi Zheng; Peng Zhao; Weijia Fang; Wenbin Chen (PLoS ONE, 2025)
Purpose This study aims to compare the safety and efficiency of modified biweekly CAPOX and conventional triweekly CAPOX in high-risk stage II and stage III post-surgery colorectal (CRC) patients. Methods From July 25, 2018, to May 14, 2021, high-risk stage II and stage III post-surgery CRC patients were randomized in the control triweekly group (intravenous infusion of oxaliplatin 130 mg/m2 on day 1 and oral capecitabine 1000 mg/m2, twice daily from day 1 to day 14) and the experimental biweekly group (intravenous infusion of oxaliplatin 85 mg/m2 on day 1 and oral capecitabine 1000 mg/m2, twice daily from day 1 to day 10). The primary endpoint was the incidence rate of thrombocytopenia. The secondary endpoint was 3-year disease free survival (DFS) rate. The patients follow up was started on July 25, 2018, and finished on October 8, 2024. Results A total of 160 patients were 1:1 randomly assigned (80 patients to biweekly group and 80 patients to triweekly group). All grade thrombocytopenia occurred in 33% and 49% patients at biweekly and triweekly group, respectively (P = 0.02). Neutropenia presented in 36% and 51% patients at biweekly and triweekly group, respectively (P = 0.04). The second endpoint 3-year DFS was 85.1% in biweekly group and 80.4% in triweekly CAPOX group (P = 0.51, HR = 0.78, [95%CI, 0.38-1.63]). The total rate of uncomplete therapy patient was 7.5% and 15% in biweekly and triweekly group, respectively (P = 0.13). Conclusion Biweekly CAPOX presented significant less thrombocytopenia and neutropenia than triweekly CAPOX regimen. There was no difference in 3-year DFS between biweekly CAPOX and triweekly CAPOX. Clinical trial registration: ClinicalTials.gov (NCT03564912).